Pengaruh Carboxymethyl Celulosa Natrium Sebagai Pengental Terhadap Stabilitas Sirup Temulawak (Curcuma Xanthorriza Roxb) - Nutrisia Aquariushinta Sayuti (Poltekkes Kemenkes Surakarta, 2016)
Abstract : Carboxymethyl celulosa natrium, Curcuma xanthorriza Roxb syrup, Stability. The lack flavor and amylum contain of Curcuma xanthorriza Roxb cause difficulty to make it in to syrup. Carboxymethyl Celulose Natrium (CMC- Na) as a thickener was needed to solve the problem. The study aim to determine the influence of CMC-Na to syrup’s stability Curcuma xanthorriza. The methode was used to determine stability of syrup formulation with three formula with variations in the amount of 1% CMC-Na solution and 80% sucrose solution. Physical stability parameter of the syrup such as viscosity, acidity and organoleptic analyzed by two way anava. The result showed that CMC-Na effected on viscosity, acidity and organoleptic of the syrup. There are influence of CMC-Na to syrup’s stability.